2009
DOI: 10.1029/2009ja014044
|View full text |Cite
|
Sign up to set email alerts
|

Entropy and plasma sheet transport

Abstract: [1] This paper presents a focused review of the role of entropy in plasma sheet transport and also describes new calculations of the implications of plasma sheet entropy conservation for the case where the plasma pressure is not isotropic. For the isotropic case, the entropy varies in proportion to log [PV 5/3 ], where P is plasma pressure and V is the volume of a tube containing one unit of magnetic flux. Theory indicates that entropy should be conserved in the ideal MHD approximation, and a generalized form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
176
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(187 citation statements)
references
References 64 publications
9
176
0
Order By: Relevance
“…We also notice that their magnitudes have a tendency to increase toward the storm maximum. The reason is that PV 5/3 in the inner magnetosphere increases as the ring current builds up; thus, the bubbles with the same amount of PV 5/3 reduction will penetrate deeper in the storm maximum than in the beginning of the storm and the perturbations also become more intense [e.g., Birn et al, 2004;Wolf et al, 2009]. …”
Section: Signatures In the Central Ring Current Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also notice that their magnitudes have a tendency to increase toward the storm maximum. The reason is that PV 5/3 in the inner magnetosphere increases as the ring current builds up; thus, the bubbles with the same amount of PV 5/3 reduction will penetrate deeper in the storm maximum than in the beginning of the storm and the perturbations also become more intense [e.g., Birn et al, 2004;Wolf et al, 2009]. …”
Section: Signatures In the Central Ring Current Regionmentioning
confidence: 99%
“…Those BBFs/bubbles are believed to account for the majority of transport in the plasma sheet [e.g., Angelopoulos et al, 1994], serving as an important mechanism for particle acceleration and transport from the magnetotail to the inner magnetosphere [e.g., Lyons et al, 2003;Birn et al, 2011;Yang et al, 2011]. They can penetrate deep into the inner magnetosphere through interchange instability [e.g., Wolf et al, 2009], which often leads to magnetic field dipolarization and particle energization during storm times [Ohtani et al, 2007;Gkioulidou et al, 2014;Turner et al, 2015]. On the other hand, numerical simulations of Lemon et al [2004] suggested that it was difficult for lossless adiabatic convection to transport a fully populated flux tube from the middle plasma sheet into the ring current region even when the cross polar cap potential (CPCP) drop is 100 kV.…”
Section: Introductionmentioning
confidence: 99%
“…Dipolarization events consist of a rapid change from stretched tail-like to more dipolar magnetic fields and are identified most commonly to be the rapid increase of B z within the central plasma sheet. Magnetic field lines threading through the region of enhanced B z are characterized by reduced field line entropy [e.g., Wolf et al, 2009;Birn et al, 2009;Yang et al, 2010;Kim et al, 2010;Dubyagin et al, 2011] and commonly denoted as "bubble" [Pontius and Wolf , 1990] or "dipolarizing flux bundle" (DFB) [Liu et al, 2013a[Liu et al, , 2013b. Earthward moving short dipolarization pulses are typically associated with an earthward flow burst [e.g., Nakamura et al, 2002;Runov et al, 2009;Sergeev et al, 2009], whereas an increase of B z toward a more persistent higher level may be observed closer to Earth without significant flow .…”
Section: Introductionmentioning
confidence: 99%
“…Bubbles are thought to be generated by magnetic reconnection in the near-Earth magnetotail [e.g., Hesse and Birn, 1991]. Other forms of current sheet disruption [e.g., Lui, 1994] during a substorm event can also generate bubbles [Wolf et al, 2009].…”
Section: Introductionmentioning
confidence: 99%